Factors Behind the Higher COVID-19 Risk in Diabetes: A Critical Review - Magdy Beshbishy, Amany; Oti, Victor B.; Hussein, Diaa E.; Rehan, Ibrahim F.; Adeyemi, Oluyomi S.; Rivero-Perez, Nallely; Zaragoza-Bastida, Adrian; Shah, Muhammad Ajmal; Abouelezz, Khaled; Hetta, Helal F.; Cruz-Martins, Natália; Batiha, Gaber El-Saber (Frontiers in Public Health, 2021)
Diabetes mellitus (DM) and coronavirus disease 2019 (COVID-19) are public health issues worldwide, and their comorbidities trigger the progress to severe disease and even death in such patients. Globally, DM has affected an estimated 9.3% adults, and as of April 18, 2021, the World Health Organization (WHO) has confirmed 141,727,940 COVID-19 confirmed cases. The virus is spread via droplets, aerosols, and direct touch with others. Numerous predictive factors have been linked to COVID-19 severity, including impaired immune response and increased inflammatory response, among others. Angiotensin receptor blockers and angiotensin converting enzyme 2 have also been identified as playing a boosting role in both susceptibility and severity to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Specifically, in DM patients, both their control and management during this pandemic is herculean as the restriction periods have markedly hampered the maintenance of means to control glycemia, hypertension, and neuroendocrine and kidney diseases. In addition, as a result of the underlyin cardio-metabolic and immunological disorders, DM patients are at a higher risk of developing the severe form of COVID-19 despite other comorbidities, such as hypertension, also potentially boosting the development of higher COVID-19 severity. However, even in non-DM patients, SARS-CoV-2 may also cause transient hyperglycemia through induction of insulin resistance and/or pancreatic β-cell injury. Therefore, a strict glucose monitoring of DM patients with COVID-19 is mandatory to prevent life-threatening complications.